Electronic Properties of SbTa1-xNbxO4: Phase-Related Distortions. Issue 5 (1st January 2019) - Bainglass, Edan; Huda, Muhammad N.
Abstract : We have studied the effects of structural symmetry related distortions on the band gaps and overall energetics of Sb M O4 compounds ( M = Ta, Nb). Evolution of the electronic structures was studied as one transitions gradually from a system of 4d bands to 5d bands, and whether this has any effect on the Sb oxidation state or its lone pair s electrons. From the atomic point of view, electronic correlation energy is higher in Ta 5d than in Nb 4d, and Nb 4d bands are higher in energy than Ta 5d. These were examined in terms of oxidation states in their respective solids and mixed alloys. We look at the effects of increasing Nb concentration on the electronic structures of SbTa1- x Nb x O4 alloys with emphasis on polyhedral interactions and overall cell distortions. We decouple the effects caused by the presence of different n d cations from those caused by distortions and reorientation of various polyhedra.